Optimization study on antioxidant in fruit extract of Phaleria macrocarpa (Scheff.) Boerl in Malaysia and evaluation on its functional cosmetic - Mohamed Mahzir, Khurul Ain (2018)
Phaleria macrocarpa (Scheff.) Boerl belong to Thymelaeceae family and widely known as ‘Crown of God’, ‘Mahkota Dewa’ and ‘Pau’. It is a native plant from the Papua Island, Indonesia and grows in tropical areas. It had been reported P.macrocarpa have traditional medicine and bioactive activities such as anti-tumor, anti-hyperglycemia, anti-inflammation, anti-diarrhoel, anti-oxidant, anti-viral, antibacterial, anti-fungal and vasodilator effect. However, there is still lacking in investigation of antioxidants by using Response Surface Methodology (RSM). Therefore,in this study to determine the antioxidants properties such as [2,2- diphenly-1-picrylhydrazyl (DPPH) free radical scavenging activity, total phenolic content (TPC), total flavonoid content (TFC) and ferric ion reducing power assay (FRAP) of P.macrocarpa fruits by using Response Surface Methodology, Central Composite Design (CCD) was applied to determine the maximum percentages yield by focusing on three independent variables which include extraction temperature (53.18- ْ 80 C), extraction time (66.30-133.64 minutes) and solvent ethanol :water ratio (63.18-96.82%v/v) with twenty experiments was carried out. The extraction was carried out manually by using reflux set apparatus and filter out the solvent manually. The optimal conditions for the antioxidants extraction were found to be extraction temperature (63.60 ºC), extraction time (66.36 minutes) and solvent of ethanol:water ratio (74.36 %v/v) with the highest percentage yield of DPPH, TPC, TFC and FRAP were 87.23%, 268.03&, 3.22% and 7.49%. Therefore, the yield of antioxidants activities obtained experimentally was close to the predicted values and suitability of the model employed in RSM to optimizing the extraction condition. In a conclusion, RSM was a good statistical tool with empower evaluation of the effects of certain process variables and their interaction of response variables in a short time, less cost and less number of required experiments.